ANALISIS KOORDINASI OVER CURRENT RELAY DAN RECLOSER DI SISTEM PROTEKSI FEEDER GARDU INDUK SEMEN NUSANTARA (SNT 2) CILACAP - Hariyanto, Dwi Puji; Tiyono, -; Sutarno, - (Jurusan Teknik Elektro, Fakultas Teknik, Universitas Negeri Semarang, 2009)
The main aim of protection system is used to protect safety of human cause by electrics current and to protect equipment from the fault. The fault can cause over current which has big value and endangerous the equipment. Besides the fault can also cause supply of energy to consumer is disturbed. The fault can be permanently or temporary. Coordination of protection system between OCR and recloser is needed to anticipate the fault.To create good coordination in protection system, the threshold setting is the main key. In determining OCR and Recloser setting, there are many effect that need attention for example the use of curve characteristic, current setting (In) and time setting (Tms)Based on reaserch data and calculation, the biggest of 3 phase short circuit over curent in feeder SNT 2 is 12 kA in the near of substation. While the smallest of 3 phase short circuit over curent in feeder SNT 2 is 1,9 kA in the tail of network. The smallest of 3 phase short circuit over curent can be detected by recloser 2.The three relays, OCR, Recloser 1 and Recloser 2 have each different graph of characteristic that is not proportioned. Its shows that the setting of three relays is correct because there isnÃ¢â¬â¢t any relay that precede the other relays.Keyword :ÃÂ Protection system, OCR, Recloser, Coordination, Fault, Feeder SNT 2.